Central and Peripheral Nervous System Progenitors Derived from Human Pluripotent Stem Cells Reveal a Unique Temporal and Cell-Type Specific Expression of PMCAs - Chen, Muwan; Laursen, Sofie H.; Habekost, Mette; Knudsen, Camilla H.; Buchholdt, Susanne H.; Huang, Jinrong; Xu, Fengping; Liu, Xin; Bolund, Lars; Luo, Yonglun; Nissen, Poul; Febbraro, Fabia; et al. (Frontiers in Cell and Developmental Biology, 2018)
The P-type ATPases family consists of ion and lipid transporters. Their unique diversity in function and expression is critical for normal development. In this study we investigated human pluripotent stem cells (hPSC) and different neural progenitor states to characterize the expression of the plasma membrane calcium ATPases (PMCAs) during human neural development and in mature mesencephalic dopaminergic (mesDA) neurons. Our RNA sequencing data identified a dynamic change in ATPase expression correlating with the differentiation time of the neural progenitors, which was independent of the neuronal progenitor type. Expression of ATP2B1 and ATP2B4 were the most abundantly expressed, in accordance with their main role in Ca2+ regulation and we observed all of the PMCAs to have a subcellular punctate localization. Interestingly in hPSCs ATP2B1 and ATP2B3 were highly expressed in a cell cycle specific manner and ATP2B2 and ATP2B4 were highly expressed in a hPSC sub-population. In neural rosettes a strong apical PMCA expression was identified in the luminal region. Lastly, we confirmed all PMCAs to be expressed in mesDA neurons, however at varying levels. Our results reveal that PMCA expression dynamically changes during stem cell differentiation and highlights the diverging needs of cell populations to regulate and properly integrate Ca2+ changes, which can ultimately correspond to changes in specific stem cell transcription states.